Changes in sexual satisfaction across three years of the transition to parenthood predicted by sexual communication and sexual esteem - May, Scott (Kansas State University, 2019)
The transition to parenthood is a time of adjustment and challenges, as parents undergo many changes in their relationship, in their lifestyle, and in their home. The nature of the couples’ romantic and sexual relationship also makes substantial shifts, such as decreases in overall relationship and sexual satisfaction during the first few years as parents. Using data from 197 German heterosexual couples transitioning to parenthood in committed relationships across three years, rates of change in sexual satisfaction of women and men were tested and assessed to what extent the expected trajectories of sexual satisfaction were linked with initial scores from both partners on sexual communication and sexual esteem using a time-invariant covariate growth curve model. Results indicated that women and men both declined in their reports of sexual satisfaction with women experiencing less of decline. Sexual communication by both women and men was the only significant predictor for positive rates of change in sexual satisfaction for women at baseline while controlling for breastfeeding, conflict, and sexual frequency. These results suggest that clinical interventions might be best focused on supporting techniques to foster sexual communication for the couple during their transition to parenthood.
Keywords: Sexual communication; Sexual esteem; Sexual satisfaction trajectories; Transition to parenthood